2016
DOI: 10.5194/acp-2016-469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can simple models predict large scale surface ocean isoprene concentrations?

Abstract: <p><strong>Abstract.</strong> We use isoprene and related field measurements from three different ocean data sets together with remotely sensed satellite data to model global marine isoprene emissions. We show that using monthly mean satellite derived chl-<i>a</i> concentrations to parameterize isoprene with a constant chl-<i>a</i> normalized isoprene production rate underpredicts the measured oceanic isoprene con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 22 publications
5
44
0
Order By: Relevance
“…Estimates from bottom-up studies, i.e., scaling up biological VOC emissions for different microorganism species, yield isoprene emissions in a similar range of 0.085–1.24 Tg yr –1 . However, it was also shown that top-down approaches, i.e., calculating isoprene fluxes by atmospheric chemistry models, suggest much larger isoprene emissions of 1.9–11.6 Tg yr –1 globally 16 , 17 , 20 , 28 , 29 . Thus, accounting for interfacial photochemistry might aid in closing, or at least minimizing, this discrepancy between bottom-up and top-down approaches in global and regional models.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates from bottom-up studies, i.e., scaling up biological VOC emissions for different microorganism species, yield isoprene emissions in a similar range of 0.085–1.24 Tg yr –1 . However, it was also shown that top-down approaches, i.e., calculating isoprene fluxes by atmospheric chemistry models, suggest much larger isoprene emissions of 1.9–11.6 Tg yr –1 globally 16 , 17 , 20 , 28 , 29 . Thus, accounting for interfacial photochemistry might aid in closing, or at least minimizing, this discrepancy between bottom-up and top-down approaches in global and regional models.…”
Section: Resultsmentioning
confidence: 99%
“…North of Mauritius the isoprene concentration steadily increased from sub 1 nmol L −1 just off Mauritius to around 30 pmol L −1 at the Maldives. The maximum values of isoprene were reached at 6.1° S and 64.45° E on day of year 2014 (DOY) 209.45 (Booge et al, ). The DMS and isoprene seawater distributions were anticorrelated over most of the cruise tracks.…”
Section: Resultsmentioning
confidence: 99%
“…However, this rate term was based on data from methyl bromide biodegradation, which was considered to be a functionally equivalent BVOC. Booge et al [ 56 ] reported that the application of a lower value for isoprene biodegradation resulted in closer correspondence between observed and simulated marine isoprene flux. The justification for doing so was based on their currently unpublished biodegradation measurements using deuterated isoprene, which gave lower values than the rate used by Palmer and Shaw [ 50 ].…”
Section: Ecology Physiology and Biogeochemistry Of The Isoprene Cycmentioning
confidence: 96%
“…Although marine emissions are low compared with those from land, they can have a disproportionately large influence on aerosol formation and the atmosphere’s oxidation capacity in remote and pristine regions [ 48 , 51 , 52 ]. This large variation in estimates of global isoprene emissions from marine environments may be explained by a number of factors that are not always sufficiently accounted for in models, including the mainly biological factors outlined here: (1) photochemically-derived isoprene, e.g., from breakdown of fatty acids in the sea-surface microlayer, which is not considered in bottom-up methods [ 53 ]; (2) limited data, including from highly productive coastal zones and different oceans and accounting for seasonal variation (e.g., [ 44 , 47 , 54 , 55 ]); (3) differences in isoprene production under variable and stressful in-situ conditions compared with laboratory cultures [ 9 , 52 ]; (4) phylogenetic and latitudinal variation in isoprene production by microalgal species [ 9 , 48 , 56 ]. Points 3 and 4 are most dramatically exemplified by Srikanta Dani et al [ 57 ], who suggest that diatoms alone emit 4.8 Tg C y −1 of isoprene, which greatly exceeds current bottom-up estimates for all taxa in marine ecosystems.…”
Section: Ecology Physiology and Biogeochemistry Of The Isoprene Cycmentioning
confidence: 99%